Deformation and microstructural development in a 2124Al/SiCpMMC during high strain rate superplasticity - Zahid, G; Todd, R; Prangnell, P (1999)
Both superplastic deformation and the accompanying microstructural development in st 2124Al/18vol%SiCp, metal matrix composite have been investigated. Mechanical property results comparable to those found in similar materials have been achieved, the optimum superplastic elongation being 430% at a strain rate of almost 0.1s(-1) . The anomalously high activation energy which has been observed in other studies was also reproduced. Differential scanning calorimetry showed that the optimum temperature in the current material was significantly below the temperature at which melting began, however, in contrast to some previous work. Microstructural investigation showed that both the optimum elongation, and the onset of the high activation energy regime, coincided with the temperature above which the majority of the intermetallic particles present at lower temperatures started to dissolve. It is concluded that the high apparent activation energy is an artefact caused by microstructural changes. The deformation and microstructural changes observed are consistent with grain boundary sliding accommodated by slip in the aluminium matrix. It is suggested that this type of deformation may occur by groups of grains surrounding SiC particles acting as a single deformation unit.